Pendampingan Pembuatan Asap Cair dari Limbah Jerami Padi untuk Bio-pestisida pada Kelompok Tani Diat 1, Bolaang Mongondow - Jannah, Miftahul; Rampe, Meytij Jeanne; Hasmiati, Hasmiati; Undap, Hizkia Abraham Febrian; B, Riska Yohana BR Nainggolan. (Universitas Nusantara PGRI Kediri, 2024)
This service activity is carried out based on observations and discussions of the community service team with partners. Where, based on the results of observations, it was found that problems had not been optimally resolved regarding rice straw waste and rice plant pests. This activity aims to provide socialization and assistance in making liquid smoke from rice straw for bio-pesticide as an effort to overcome problems experienced by partners. The partners or participants in this activity are the “Kelompok Tani Diat I”, numbering 15 people. The stages of this activity are the observation stage, technology design, tool testing, socialization, assistance and evaluation. Mentoring activities are carried out using the PLA (Participatory and Learning Action) method and science and technology diffusion. Participants are given pre and post tests to measure the participant's level of understanding of the training material. This service activity produces grade 3 liquid smoke and liquid smoke pyrolysis equipment which is handed over to partners. Apart from that, partners also gained a 51% increase in knowledge and skills regarding the training material presented in this service activity.